2023
DOI: 10.1002/bmm2.12026
|View full text |Cite|
|
Sign up to set email alerts
|

Prosthetic heart valves for transcatheter aortic valve replacement

Abstract: Transcatheter aortic valve replacement (TAVR) has the advantages of less trauma and faster postoperative recovery, which has brought the possibility to the elderly patient with valvular heart disease and is gradually replacing surgical aortic valve replacement (SAVR). The interventional valve used in TAVR needs to be compressed and transported through the catheter to the lesion site, and can still recover its original shape, structure and performance. This process requires that the material should be flexible,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 151 publications
0
2
0
Order By: Relevance
“…To avoid its rejection, cellular antigen and nucleic acid residues are removed (i.e., to decellularize biomaterials-to remove cells and nucleic acids in the extracellular matrix to reduce the immunogenicity of biomaterials from non-autologous sources). Several studies have shown that the combined decellularization method can not only increase the decellularization efficiency but also maximize the protection of the extracellular matrix [114,115], which prevents calcification.…”
Section: Advanced Developments In the Field Of Heart Valvesmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid its rejection, cellular antigen and nucleic acid residues are removed (i.e., to decellularize biomaterials-to remove cells and nucleic acids in the extracellular matrix to reduce the immunogenicity of biomaterials from non-autologous sources). Several studies have shown that the combined decellularization method can not only increase the decellularization efficiency but also maximize the protection of the extracellular matrix [114,115], which prevents calcification.…”
Section: Advanced Developments In the Field Of Heart Valvesmentioning
confidence: 99%
“…First, they can be mass-produced compared to the limited sources and high cost of biological valves, and second, they have precisely regulated physical and biochemical properties. However, the greatest challenges for them remain prosthesis failure due to the difference in elastic modulus between polymers and native tissue and durability [115,118,119].…”
Section: Advanced Developments In the Field Of Heart Valvesmentioning
confidence: 99%